Mechanical Characterization of Intermediates of Ag+-Dna Complex: An Atomic Force Study - Melo-Hurtado, F (AIP Publishing, 2025)
Silver ions (Ag+) are known to interact with DNA through nonspecific and specific mechanisms, inducing conformational and mechanical changes in the double helix. In this study, we investigate how varying Ag+ concentrations affect the mechanical properties of DNA, in particular, contour length, persistence length, end-to-end distance, and area of occupation, using atomic force microscopy. At low Ag+ concentrations, we observe localized stiffening and shortening of DNA molecules, which we attribute to the formation of monoadducts and biadducts with specific DNA bases. These interactions promote the emergence of secondary structures that contribute to DNA compaction and a reduction in contour length. At intermediate concentrations, accumulation of torsional stress and the formation of multiple metal-mediated contacts lead to a global conformational collapse, as evidenced by a significant decrease in the effective persistence length. At the highest Ag+ concentration tested (1.5 mM), the uniform distribution of molecular area suggests a widespread structural collapse of DNA. These findings support previous reports of Ag+-induced DNA condensation and reveal a progressive structural transition from extended to globular conformations. The observed behavior provides insights into the biophysical consequences of metal-DNA interactions and may have implications for understanding the molecular basis of the antimicrobial activity of silver ions.